Perancangan produk figur aksi dalam perspektif desain interaksi sebagai media pengenalan kesenian Ulin Barong Sekeloa - Chris Chalik; Nurul Fitriana Bahri; Martiyadi Nurhidayat; Sina Saumi Al Ahmad; Adrian Permana Zen (Institut Seni Indonesia Yogyakarta, 2026)
This study is entitled Designing Action Figures from an Interaction Design Perspective as a Medium for Introducing Ulin Barong Sekeloa Art. The case study was conducted at Telkom Buah Batu Kindergarten in Bandung, as this action figure product is intended for kindergarten-aged children as the main target audience. Ulin Barong Sekeloa art was chosen as the object of representation to introduce local culture through a medium that is interesting, easy to understand, and appropriate for children's cognitive development stage. The research methods included classroom observation, interviews with teachers, and observation of children's interactions with the action figure prototypes. Interaction design principles were applied to create an education-based play experience that involved touch, shape manipulation, and simple visual responses. The results of the study show that action figures designed with a product and interaction design approach can increase children's engagement, curiosity, and initial understanding of the characteristics of Ulin Barong Sekeloa. This product has the potential to be an effective medium for cultural learning as well as a means of preserving traditional arts in early childhood education/ Published Date: 2026-07-30